2020
DOI: 10.3390/cancers12061531
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Comparison of HPV-Positive and HPV-Negative Oropharyngeal Cancer

Abstract: Squamous cell carcinoma of the head and neck (HNSCC) consist of two distinct biological entities. While the numbers of classical, tobacco-induced HNSCC are declining, tumors caused by human papillomavirus (HPV) infection are increasing in many countries. HPV-positive HNSCC mostly arise in the oropharynx and are characterized by an enhanced sensitivity towards radiotherapy and a favorable prognosis. To identify molecular differences between both entities on the protein level, we conducted a mass spectrometric c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 111 publications
0
12
0
Order By: Relevance
“…In addition, its overexpression was found to be associated with liver cancer cell migration, which may promote the progression of liver cancer ( 36 ). Some studies have found that SLC3A2 has a carcinogenic effect in many kinds of cancers, including oropharyngeal cancer ( 37 ), head and neck squamous cell carcinomas (HNSCC) ( 38 , 39 ), and renal cancer cell ( 40 ), which contributes to inferior prognosis of cancer patients, and may act as a predictive marker. RAF1 is a kind of gene known as an oncogene, which is a part of the RAS/MAPK pathway, and is closely related to the progression of a variety of tumors and can be a potential key target of cancer therapy ( 41 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, its overexpression was found to be associated with liver cancer cell migration, which may promote the progression of liver cancer ( 36 ). Some studies have found that SLC3A2 has a carcinogenic effect in many kinds of cancers, including oropharyngeal cancer ( 37 ), head and neck squamous cell carcinomas (HNSCC) ( 38 , 39 ), and renal cancer cell ( 40 ), which contributes to inferior prognosis of cancer patients, and may act as a predictive marker. RAF1 is a kind of gene known as an oncogene, which is a part of the RAS/MAPK pathway, and is closely related to the progression of a variety of tumors and can be a potential key target of cancer therapy ( 41 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…CCT8 has been detected in several types of cancers, such as esophageal squamous cell carcinoma (69), hepatocellular carcinoma (70), and B-cell non-Hodgkin's lymphoma (71). Wurlitzer et al performed a mass spectrometric comparison of HPV-positive and HPV-negative oropharyngeal tumors and identified differentially expressed proteins, such as CCT8, in HPV-positive samples reflecting enhanced migration and invasion (72). Results show an underexpression of the ALDHA1A and CCT8 genes in the E-A176/G350 and AAa variants when compared to the prototype, however, at the protein level they showed the highest levels of expression (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting reports on the correlation between CSC population and HPV status, which may be attributed to the analysis of different CSC markers in different studies 17‐22 (Table S6). Limited studies have comprehensively analyzed different CSC markers in clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with HPV‐positive tumors are speculated to be associated with improved treatment outcomes as the tumor may harbor a decreased number of CSCs. However, there are conflicting reports on the correlation between the CSC population and HPV status 17‐22 . The elucidation of the molecular profiles of HPV‐negative, HPV‐positive, and p16‐positive/HPV‐negative HNSCCs is necessary for successful disease management.…”
Section: Introductionmentioning
confidence: 99%